2022
DOI: 10.3389/fcimb.2022.790184
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Group Distribution of Uropathogenic Escherichia coli and Related Antimicrobial Resistance Pattern: A Meta-Analysis and Systematic Review

Abstract: The phylogenetic classification of Escherichia coli isolates is of great importance not only for understanding the populations of E. coli but also for clarifying the relationship between strains and diseases. The present study aimed to evaluate the prevalence of phylogenetic groups, antibiotic susceptibility pattern, and virulence genes among uropathogenic E. coli (UPEC) isolated from different parts of Iran through a systematic review and meta-analysis. Several international electronic sources, including Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 66 publications
5
34
1
Order By: Relevance
“…So, figuring out the types of antibiotic resistance, how they spread, the characteristics of resistant bacteria, and the clonal relationships between isolates can help make treatment guidelines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, figuring out the types of antibiotic resistance, how they spread, the characteristics of resistant bacteria, and the clonal relationships between isolates can help make treatment guidelines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the risk factors for MDR, ESBLs-producing and carbapenem-resistant GNBSI in this study provide possibilities to prevent such kind of GNBSI. 55 …”
Section: Discussionmentioning
confidence: 99%
“…Overall, the risk factors for MDR, ESBLs-producing and carbapenem-resistant GNBSI in this study provide possibilities to prevent such kind of GNBSI. 55 Our study has some limitations. Firstly, this research was conducted in a single center, and we used the retrospective observational study.…”
mentioning
confidence: 89%
“…These results confirm previous findings worldwide [8], highlighting a relationship between biofilm production and phylogenetic groups B2 and D. As previously argued, it is very challenging to work out how this relationship works as there several other competing factors. For example, multidrug resistance tends to be confined to these phylogenetic groups [37,38] as well as a multiplicity of other VFs, all of which have been linked to biofilm production). We have previously shown that group B2 strains on average carry more VF genes than other groups, and hence argue that probably the phylogeny forms the basis for virulence in UPEC [39].…”
Section: Discussionmentioning
confidence: 99%